Microbiota and nutrition as risk and resiliency factors following prenatal alcohol exposure - Upreti, Deepa; Rouzer, Siara K.; Bowring, Abigail; Labbe, Emma; Kumar, Rosaline; Miranda, Rajesh C.; Mahnke, Amanda H. (Frontiers in Neuroscience, 2023)
Alcohol exposure in adulthood can result in inflammation, malnutrition, and altered gastroenteric microbiota, which may disrupt efficient nutrient extraction. Clinical and preclinical studies have documented convincingly that prenatal alcohol exposure (PAE) also results in persistent inflammation and nutrition deficiencies, though research on the impact of PAE on the enteric microbiota is in its infancy. Importantly, other neurodevelopmental disorders, including autism spectrum and attention deficit/hyperactivity disorders, have been linked to gut microbiota dysbiosis. The combined evidence from alcohol exposure in adulthood and from other neurodevelopmental disorders supports the hypothesis that gut microbiota dysbiosis is likely an etiological feature that contributes to negative developmental, including neurodevelopmental, consequences of PAE and results in fetal alcohol spectrum disorders. Here, we highlight published data that support a role for gut microbiota in healthy development and explore the implication of these studies for the role of altered microbiota in the lifelong health consequences of PAE.